Початки досліджень історії права Київської Русі на українських землях у1810-х рр. - Греченко, В.; Grechenko, V.; Ярмиш, О.; Yarmysh, O. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті аналізується перша публікація з історії Давньої Русі, видана у Харкові у 1811-1812 рр., де також уперше на українських землях розглядалися деякі аспекти історії права доби Київської Русі. Розглядається та оцінюється науково-педагогічна діяльність професора історії Харківського університету Г.П. Успенського, який був автором цієї публікації. Його праця не була чисто історико-правовою. Вона містила не тільки елементи історико-правових досліджень, але це був певний етап у розвитку вітчизняної науки історії права.The article deals with the main aspects of the pedagogical activity and scientific achievements of G.P.Uspenskyi, professor of history at Kharkiv University, who was the first in Ukraine to begin the study of the history of law of the Kiyivan Rus era, and describe it in his work «The Experience of the Narrations on the Russians Antiquities» published in 1811-1812. By recently there have been no publications revealing the scientific work of G.P.Uspenskyi. The scientist worked at Kharkiv University from 1807 until his death in 1820. In his work he analyzes the content of the laws of Kyivan Rus, the essence of which he described in 8 points. G.P. Uspenskyi emphasizes the importance of oath in the legal proceedings, the availability of the death penalty for some crimes, the right of a wife to inherit the property of her husband, punishment of a wife for the crime of a husband, and children for the crime of their father; a wound inflicted with a weapon, not to be punished by deprivation of the body organ for the body organ but imposing a monetary penalty; it was allowed to kill the thief who was caught at the crime scene, if it was impossible to hold and tie him; the property of a foreigner who died without a will had to be returned to his homeland for the transferto his relatives, and was not charged in favor of the state. G.P. Uspenskyi also thought that the term «plot» («vidok») meant the same thing as the witness, who saw himself how the crime was committed, and the term «rumor» («posluh») testified, that he had heard about it from others. Views of G.P.Uspensky largely coincide with the modern ones. His work was not purely historical or legal. It contained only elements of historical and legal research, but in fact, it was a certain stage in the development of the research in the history of law. Herewith, the professor relied on some achievements of the then historical-legal science, particularly, on the comments to the editions of the Ruska Pravda in 1792 and 1799.
Beginnings of the Researchon the History of Law of Kyivan Rus and Its Enforcement on the Ukrainian Lands in the 1810's.
Keywords: Україна; Харківський університет; історія права; Київська Русь; Руська Правда; Г.П. Успенський; Ukraine; Kharkiv University; history of law; Kievan Rus; Ruska Pravda; G.P. Uspenskyi